2022
DOI: 10.3390/molecules27196561
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Solid-Phase Micro-Extraction Versus Hydrodistillation of Volatile Compounds from Leaves of Cultivated Mentha Taxa: Markers of Safe Chemotypes

Abstract: Various mint taxa are widely cultivated and are used not only for medicinal purposes but also in cosmetic and industrial applications. The development of new varieties or cultivars of mint generates difficulties in their correct identification and safe use. Volatile organic compounds (VOCs) from the leaves of seven different taxa of the genus Mentha obtained by hydrodistillation (HD) and headspace solid-phase microextraction (HS-SPME) were analyzed using gas chromatography–mass spectrometry (GC-MS). Principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Some temperature-sensitive volatiles can be degraded when high temperatures are used during the analysis, which is eliminated in the HS-SPME. Adam et al (2022) also confirmed that more volatile components were detected using HS-SPME than hydro-distillation in Mentha species [ 66 ]. Moreover, semi-volatiles, such as oxygenates and some hydrocarbons, were also detected in this study, but had not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Some temperature-sensitive volatiles can be degraded when high temperatures are used during the analysis, which is eliminated in the HS-SPME. Adam et al (2022) also confirmed that more volatile components were detected using HS-SPME than hydro-distillation in Mentha species [ 66 ]. Moreover, semi-volatiles, such as oxygenates and some hydrocarbons, were also detected in this study, but had not been reported in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…In the characterization of VOCs from plant matrices, the sample preparation and detection techniques are critical steps in achieving optimal results [ 65 , 66 ]. Nowadays, headspace solid-phase microextraction (HS-SPME) sample preparation coupled with gas chromatography/time-of-flight mass spectrometry (GC-TOF-MS) has been widely employed for metabolic profiling of volatiles from highly complex plant matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported method was used with slight modifications. 28,29 The volatile compounds were extracted using a solid-phase (SPME) microextraction device, configured with 50/30 μm divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) (Supelco, Bellefonte, PA, U.S.A.) fibers. First, 5 g of peanut oil and 2 g of peppermint oil were weighed into a 20 mL headspace vial and sealed with an aluminum cap and Teflon silicone septum.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies focus on the application of microwaves as a technique for extracting essential oils from peppermint [ 13 , 16 , 24 , 25 ]. The novelty of this study consists in the application of microwaves with the aim of making the extraction process of bioactive compounds such as polyphenols and peppermint pigments more efficient.…”
Section: Introductionmentioning
confidence: 99%